Beyond GDP: Lessons for Redefining Progress in Canadian Food System Policy - Robert, Naomi; Mullinix, Kent (Frontiers in Communication, 2022)
Gross Domestic Product (GDP), while initially conceived to measure economic activity, is now the most widely used indicator for societal progress and wellbeing. Its contemporary (mis)use as has been documented and discussed in Beyond GDP research. This mini-review offers a food systems lens to Beyond GDP research by providing an overview of the limitations of GDP as an indicator of wellbeing, and by illustrating examples of how these are embodied in Canadian food system policy. We offer a brief summary of some established and emerging areas of research dedicated to improving assessments of societal wellbeing in policy development. We highlight connections between Beyond GDP research and advocacy for food system policy reform and suggest that strengthening connections between the two areas of research and advocacy can help center societal wellbeing within food system policy research and development in Canada.